Pengaruh Latihan Fisik dan Terhadap Penurunan Tingkat Stress Pada Mahasiswa Tingkat Akhir : Literature Review - Eka Duwi Sridevi; Jihan Sarguma Arfendi; Dini Nur Alpiah (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
Depression is widespread among adolescents and seriously harms students' quality of life and academic performance. To defend yourself in overcoming stress, you can use physical exercise. This research aims to determine the effect of physical exercise on stress levels in office working mothers. The research method with a literature review was carried out using the PICO search on the Google Scholar database. This shows that the more often physical exercise is carried out by students, the lower the stress level will be, the better the quality of life and academic performance will be, so that there is an influence of physical exercise on reducing stress levels in students due to doing physical exercise when they have a lot on their minds. and stress is able to reduce thoughts and felt stress. The results of the analysis show that physical exercise has a positive effect on reducing stress in students.